PASTORAL INOVATIF DAN KETERLIBATAN OMK MILENIAL DALAM KEGIATAN GEREJA - Amal, Yohanes; Midun, Hendrikus; Habur, Agustinus Manfred (Lembaga Penelitian STKIP Widya Yuwana, 2024)
Pastoral activity is a form of church service to the lives of the people. The quality and innovation of pastoral activities affect the involvement of parishioners in church activities. This study aims to describe the forms of pastoral innovation in St. Francis of Assisi Parish in Karot Diocese of Ruteng and their influence on the involvement of young Catholics in church activities. This type of research is descriptive qualitative. Data collection techniques using structured interviews. The research subjects consisted of ten young Catholics, parish priests and parish pastoral councils. Data analysis follows four steps: data reduction, data presentation/display, conclusions and verification. The results of the study show that Saint Francis Assisi Karot Parish in Ruteng Diocese has attempted to carry out pastoral innovations in the five main activities of the church, namely consecration (liturgy), preaching, service, communion, and martyrdom. Innovation activities in five activity areas can encourage and increase the involvement of young Catholics in church activities. This finding has implications for the church's pastoral policies and forms of youth development in the future.